Talent identification and development in soccer: An update and contemporary perspectives - Williams, A. M. (Journal of Sports Sciences, 2020)
A strong response was received to the call for submissions that was published on the journal`s website and in this special issue 28 different papers are presented, encompassing a very eclectic field of papers related to sports science and soccer/football - the latter terms are used interchangeably. The papers are spread across two volumes of the journal and an effort is made to present them in loose theme areas or clusters. The original special issue in 2000 contained only 12 papers, so the exponential growth to 28 papers, spreading across two issues, testifies to the growing popularity of the topic, the popularity of sports science generally, and expansion of the journal itself, which only published 12 issues a year at that time compared to the current 24 per annum.